Estimation of the Serum and the Salivary Trace Elements in OSMF Patients - Manasi Ankolekar Kode (Journal of Clinical and Diagnostic Research, 2013)
Objectives: Gutkha packets contain trace elements like copper, zinc, iron and magnesium. This study compared the levels of the trace elements in patients with gutkha eating habits with or without oral submucous fibrosis and in healthy patients. Study Design: A total of 75 patients were included in this study and they were divided into three groups; the individuals with a history of gutkha intake with OSMF, the individuals with a history of gutkha intake without OSMF and apparently healthy individuals without OSMF and without any habits. Blood and saliva was collected and they were subjected for analysis by using atomic absorption spectrometry and a differential pulse anodic stripping voltmeter. Results: The results were tabulated and they were subjected to a statistical analysis. Conclusion: There was a significant difference in the serum Mg and Fe levels between the patients with habits and the normal healthy individuals. A significant difference was observed in the serum zinc levels in the patients with habits with and without OSMF. Altered serum trace element levels are documented in malignant cases and they are considered to be good biomarkers for malignancies. The serum copper and Zn levels and the Cu/ Zn ratio in OSMF patients can be considered as the markers which show a susceptibility towards cancer.